Implementation of the Forward Chaining Method in Identifying Study Programs Based on Students Interests and Talents - Raudhatul Fazira; Bustami; Rizki Suwanda (Jurnal Inotera, 2025)
This study aims to develop a decision support system (DSS) based on the Forward Chaining method to assist prospective students in selecting a study program that aligns with their interests, talents, and abilities. The system is designed to analyze 34 facts related to the respondents' interests and talents using predefined Rules, generating program recommendations in the form of rankings based on suitability weights. Testing was conducted with 100 respondents, one of whom, named Najmil Ula, was recommended to choose the Chemical Engineering program with a suitability weight of 2,3 or 26.44%, based on fulfilled facts such as an interest in understand in physics and love doing an experiment. Additionally, the system provided alternative recommendations, such as Informatics Engineering and Arcitecture, with lower suitability levels. These results demonstrate that the system can provide relevant and objective recommendation, making it an effective tool to support prospective students in selecting study programs that match their potential.